“Basal Cell Carcinoma And Reconstructive Surgery” (A Study of 150 Cases) - Dr. R. G. Yadav; Dr. B. S. Chandalia (Indian Journal of Plastic Surgery)
An analysis of the 150 cases of basall cell carcinoma seen at plastic surgery department at Jaipur are reported. 112 cases were treated by surgery with a recurrence rate of 2-3% while radiotherapy had high recurrence rate of 20%, Surgery is better modality of treatment as it has got a much better cure rate.